Near-surface distribution of pollutants in coastal waters as assessed by novel polyethylene passive samplers. Issue 1 (15th June 2017) - Aminot, Yann; Belles, Angel; Alary, Claire; Readman, James W.
Abstract: We report a novel and inexpensive method to provide high resolution vertical measurements of temporally integrated organic contaminants in surface and sub-surface waters in polluted coastal environments. It employs a strip of polyethylene deployed as a passive sampler. Verifications are confirmed via conventional spot sample analyses and against Performance Reference Compound (PRC) calibration methods. Analytes targeted include 16 Polycyclic Aromatic Hydrocarbons, 15 personal care products, 8 organophosphorus flame retardants, 4 antifouling 'booster' biocides and 15 n-alkanes. Whilst all contaminants typically revealed homogeneous concentrations from 10 cm to 3 m depth in the selected harbour (< 30% variations), many increased sharply at the air-sea interface. The passive sampler was shown to afford better resolution than could be achieved using conventional analytical techniques at the surface microlayer (SML). Whilst hydrophobicity appeared to be a key factor for the enrichment of many determinants, less correlation was found for the emerging contaminants. Graphical abstract: Highlights: 3 m long polyethylene passive samplers exposed in coastal waters High resolution subsurface measurements by centimetric slicing of the samplers Contaminants concentrated in the sea surface microlayer Enrichment factors are compound-dependent.